Gender and generation: A Necessary Conceptual Clarification - González, Luis Armando (2020)
The author makes a review of the concepts gender and generation with the purpose of evince the confusion that exist in their use. He proposes to take as framework the criterion that the natural sciences follow, especially in the evolutionary biology, for define them. He poses that the notion of generational cohort it’s more useful that the idea of generation, when analyzing the generational tissue on a specific moment or over time.